An Integrative Medicine Is Prudential Hope for Covid-19 Therapeutics - dimri, Mayank; Pawar, Rajendra Singh; Rajwar, Virbal Singh; Kush, Luv (Asian Journal of Pharmaceutical Research and Development, 2020)
The human body is an integrated system. The prudential co- operation of antiviral herbs, vitamins and homeopathic products are economically feasible offer of complementary medicine to COVID-19 therapeutics.